MEMBANGUN KEGOTONGROYONGAN DAN MENGAKTIFKAN PERAN KEPEMIMPINAN LOKAL: Strategi Pentahelix Penanganan Dampak Covid-19: PENTAHELIX'S STRATEGY FOR HANDLING THE IMPACT OF COVID-19 - Muhammad Alie Humaedi; Sri Sunarti Purwaningsih; Letsu Vella Sundari; Rusdyan Fathy (LIPI Press, 2021)
The Covid-19 pandemic has plunged Indonesian society and high socio-economic vulnerability. The government through policies and programs tries to overcome the impact of the pandemic and restore people's lives. Many other parties have contributed to handling the pandemic, but they are still sectoral. In its implementation, there is still a role gap, especially the role of the government is more prominent, while the participation of various parties, especially the community is still minimal. In fact, these steps have not yielded maximum results. This can be seen from the increasing number of pandemic exposures. One of the strategies for handling a pandemic that is quite effective is the effort to accommodate social capital within the pentahelix framework. This study shows that mutual cooperation and local leadership are the dominant features of social capital practices in Indonesia. In this case, the practice of mutual cooperation, both in an organic and systematic sense, is a thread of synergy and integration among stakeholders. Therefore, packaging and strengthening social capital in policies with the pentahelix framework is the